In Situ Exsolved Nanoparticles on La0.5Sr1.5Fe1.5Mo0.5O6-δ Anode Enhance the Hydrogen Oxidation Reaction in SOFCs. Issue 2 (23rd January 2020) - Qi, He; Xia, Fang; Yang, Tao; Li, Wenyuan; Li, Wei; Ma, Liang; Collins, Gregory; Shi, Wangying; Tian, Hanchen; Hu, Shanshan; Thomas, Tony; Sabolsky, Edward M.; et al.
Abstract : In situ exsolution of nanoparticles is widely considered as an efficient and cost-effective method for increasing the number of active sites and consequently the catalytic activity on ceramic anodes in solid oxide fuel cells (SOFCs). In this study, by doping on the A-site of Sr2 Fe1.5 Mo0.5 O6- δ (SF1.5 M), evenly distributed Fe nanoparticles (∼100 nm) were exsolved on the La0.5 Sr1.5 Fe1.5 Mo0.5 O6- δ (LSFM) surface under a typical anode operating environment (humidified H2, 800 °C). In addition, the exsolution–dissolution reversibility of the exsolved Fe nanoparticles was observed during a redox cycle. Electrical conductivity relaxation (ECR) analysis demonstrated that the surface reaction kinetics on the LSFM anode is enhanced by in situ exsolution. Based on electrochemical impedance spectroscopy (EIS) and distribution of relaxation time (DRT) analysis, the perovskite structure was not damaged by the exsolution or the surface phase transition. During exsolution, the ionic conductivity increased. The higher surface catalytic activity and faster oxygen transportation led to enhanced electrochemical performance.